PROCEDURE OF BABYGRAM EXAMINATION WITH DIANGNOSIS OF TRANSIENT TACHYPNEA OF THE NEWBORN (TTN) IN PEKANBARU MEDICAL CENTRAL HOSPITAL - Siti Noer Inayah; Teguh Ilhami; Nurhikmah (Medical Imaging and Radiation Protection Research Journal, 2026)
Background: Transient Tachypnea of the Newborn (TTN) is one of the causes of respiratory distress in neonates and is associated with delayed clearance of fetal lung fluid after birth. Babygram radiography can assist in evaluating both the thoracic and abdominal conditions of neonates. Theoretically, babygram examination may be performed using anteroposterior (AP) and lateral projections; however, in clinical practice, the selection of projections may be adjusted according to the patient's condition and the purpose of the examination. To determine the management of babygram examination in neonates diagnosed with TTN at Pekanbaru Medical Center Hospital.Methods: This study employed a qualitative descriptive method with a case study approach. Data were collected through observation, interviews, and documentation of the babygram examination performed on a patient with a clinical diagnosis of TTN. Data were analyzed interactively and presented narratively.Results: Babygram examination in patients with a clinical diagnosis of TTN does not require special preparation. The patient is positioned supine on the cassette using an anteroposterior (AP) projection, with collimation adjusted to the area of interest and the central ray directed toward the xiphoid process. The exposure factors used were 48 kV and 7 mAs. The examination used only the AP projection because it was considered sufficient to demonstrate the respiratory and digestive systems on a single radiograph while taking into consideration the neonate's respiratory distress.Conclusion: The management of babygram examination in patients with a clinical diagnosis of TTN at Pekanbaru Medical Center Hospital is performed using a single AP projection without an additional lateral projection. The use of a single projection is adjusted to the patient's clinical condition and diagnostic requirements.